Dissolved inorganic carbon, alkalinity, temperature, salinity and other variables collected from discrete sample and profile observations using Alkalinity titrator, CTD and other instruments from DISCOVERY in the English Channel, Inner Sea - West Coast Scotland and others from 2011-06-06 to 2011-07-09 (NCEI Accession 0157451) - Bakker D.C.E., M. Ribas-Ribas, G. A. Lee, M. R. Palmer and M. C. Stinchcombe (NOAA NCEI Environmental Data Archive, 2016)
NCEI Accession 0157451 includes chemical, discrete sample, physical and profile data collected from DISCOVERY in the English Channel, Inner Sea - West Coast Scotland, Irish Sea and St. George's Channel, North Atlantic Ocean, North Sea and Skagerrak from 2011-06-06 to 2011-07-09. These data include DISSOLVED INORGANIC CARBON (DIC), HYDROSTATIC PRESSURE, Potential temperature (theta), SALINITY, TOTAL ALKALINITY (TA), WATER TEMPERATURE, phosphate and silicate. The instruments used to collect these data include Alkalinity titrator, CTD, Coulometer for DIC measurement and bottle. These data were collected by Mariana Ribas-Ribas of Carl von Ossietzky University of Oldenburg, Dorothee C. E. Bakker and G. A Lee of University of East Anglia; School of Environmental Sciences and M. C. Stinchcombe and M. R. Palmer [affiliation unknown] as part of the UKOA_D366_Discrete data set. CDIAC associated the following cruise ID(s) with this data set: UKOA_D366